2004
DOI: 10.1182/blood-2003-12-4396
|View full text |Cite
|
Sign up to set email alerts
|

Perturbed myelo/erythropoiesis in Lyn-deficient mice is similar to that in mice lacking the inhibitory phosphatases SHP-1 and SHIP-1

Abstract: ultimately lead to splenomegaly and myeloid neoplasia. In this study, we demonstrate that loss of Lyn results in a stem/ progenitor cell-intrinsic defect leading to an age-dependent increase in myeloid, erythroid, and primitive hematopoietic progenitor numbers that is independent of autoimmune disease. Despite possessing increased numbers of erythroid progenitors, and a more robust expansion of these cells following phenylhydrazine challenge, Lyn-deficient mice are more severely affected by the chemotherapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
106
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 58 publications
(99 reference statements)
10
106
0
Order By: Relevance
“…In macrophages, loss of Lyn results in hypersensitivity to GM-CSF and M-CSF [19,34]. Previous studies have also shown that deficiency of Lyn in aged mice results in extramedullary hematopoiesis, as well as macrophage tumors in some cases [19,38]. Our studies reveal a positive role for Lyn in regulating long-term engraftment of stem cells.…”
Section: Discussionsupporting
confidence: 72%
“…In macrophages, loss of Lyn results in hypersensitivity to GM-CSF and M-CSF [19,34]. Previous studies have also shown that deficiency of Lyn in aged mice results in extramedullary hematopoiesis, as well as macrophage tumors in some cases [19,38]. Our studies reveal a positive role for Lyn in regulating long-term engraftment of stem cells.…”
Section: Discussionsupporting
confidence: 72%
“…Importantly, the absence of Lyn, or prolonged activation of Lyn, have deleterious consequences for the hemopoietic compartment in vivo (26,27,55). The data presented here add to the understanding of the intricate mechanisms involved in the control of Src family kinases.…”
Section: Discussionmentioning
confidence: 76%
“…Lyn remains an active kinase in erythrocytes, and is capable of phosphorylating the structural protein Band 3 (25). The effects of Lyn on erythroid cells are not restricted to in vitro systems, as Lyn Ϫ/Ϫ mice display extramedullary stress erythropoiesis and eventually become anemic (26,27).…”
mentioning
confidence: 99%
“…41 In fact, LYN knockout mice are anemic. 42 Although there is no clear clinical link between Src inhibition by dasatinib and myelosuppression, nilotinib, which does not inhibit the Src family of kinases, has a more favorable myelosuppression profile. Further, a review of clinical trial data reveals that rates of grade 3/4 hematologic AEs for dasatinib treatment were higher than those seen with nilotinib in both CML-CP and CML-advanced phase (AP) patients.…”
Section: Src Kinase Inhibition: Myelosuppressionmentioning
confidence: 99%